Linguostylistic Approach to Qasidas by Ahmad Khatem Aqowalīzāde - Gačanin, Sabaheta (Prilozi za orijentalnu filologiju, 2017)
Linguostylistic research implemented in this paper focused on the linguistic features of qasida, written in Persian language by Ahmad Khatem Aqowalīzāde (Bjelopoljak), on the analysis of the stylistic figures in his qasidas and their stylemec features, i.e. the organizational structure of the linguistic expression, and the ways the stylemec constructions and figurativeness have been formed.